Outlaw red : son of Big Red - Kjelgaard, Jim, 1910-1959. (New York : Bantam books, 1977)
"This is the story of Big Red's prize-winning son, Sean, who won his greatest trophy as an outlaw in the wilderness."
Keywords: Dogs -- Fiction